Automated and Intelligent Vocational Guidance System for Classifying Specialties Based on POSCOMP Microdata - Costa, Jean Carlos; Santos, Reginaldo (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2024)
The National Examination for Admission to Postgraduate Studies in Computing (POSCOMP) is administered by the Brazilian Computer Society (SBC) to assess candidates’ knowledge for postgraduate programs in Computer Science in Brazil. Being one of the main evaluative instruments, the results of the POSCOMP exam, i.e., the database, can potentially obtain relevant patterns about the participants. In this sense, this article aims to propose an automated and intelligent vocational guidance system. This vocational system guides the participants to follow a research specialty based on the performance obtained in the exam. The proposed approach aims to support students in their academic decisions.